GPS assisted helicopter photogrammetry for highway profiling - Joy, Christopher Iain Harold (1998)
Roads are an integral part of today's lifestyle. Indeed, a modern and efficient economy requires a satisfactory road network. The road network in the United Kingdom faces ever-increasing demands with 94% of passenger travel and 92% of freight transport undertaken by road. Maintenance of the network is essential. Prior to the commencement of any maintenance scheme, an accurate highway profile is measured by undertaking a detailed topographic survey of the road surface and the adjacent verges. Traditionally, this is carried out by land surveyors using, for example, a theodolite, EDM and level.